The History of the Remains of the Roman Emperor, Julian the Apostate - Pająkowska-Bouallegui, Anna (Studia Ceranea, 2019)
Julian (Flavius Claudius Iulianus), called the Apostate, Roman emperor in the years 361–363, was one of the most intriguing rulers. From antiquity to the present day he invariably aroused great interest, both during his life and after his death. He was a just emperor, a wise commander, and a very talented writer. On 26 June 363 Julian the Apostate was mortally wounded during a battle with the Persians. He spent the last moments of his life discussing with philosophers Priskus and Maksimus the nobility of the soul, as we learn from the historian Ammianus Marcellinus. The ruler then showed, perhaps too ostentatiously, his greatest passion: love of virtue and fame. Julian the Apostate died at the age of thirty-two after only twenty months of his rule. Julian’s body, as Gregory of Nazianzus recalls, was transported from Nisibis to Tarsus in Cilicia, which took fifteen days. The subjects greeted the arrival of the body with a mournful lament or contemptuous insults, as the Father of the Church adds. Julian wanted to rest after death in Tarsus, in a mausoleum next to a small temple on the banks of the Cydnus River. Then, at an unspecified time, as the chronicler Zonaras recalls, the body of Emperor Julian the Apostate was transferred to Constantinople and buried in the Church of the Holy Apostles. Constantine Porphyrogenitus in his collection On the ceremonies of the imperial court (book II, chapter 42) mentions the grave of Julian. Today one of the porphyry sarcophagi, kept in the Archaeological Museum in Istanbul, is sometimes considered the Julian sarcophagus. The theme of this article is an attempt to determine the posthumous fate of Emperor Julian the Apostate’s body, i.e. when and in what circumstances it was transferred to Constantinople.